The Practices and Issues on Expatriate Management from Four Malaysian Human Resource Managerial Personnel's Point of View - Cheam Sheue Jin, Sheue Jin (Universiti Malaysia Sarawak, (UNIMAS), 2009)
As organisations become globalised, there is an increasing need to employ expatriates for global assignments. Investigate the practices and issues in the expatriation process from different perspectives are of utmost important to enhance understanding and improve performance of the companies in global world. This study has used a qualitative approach with the purpose to investigate the opinions from four Malaysian Human Resource Managerial Personnel regarding the expatriate management in the Multinational Companies' subsidiaries. Research areas include the expatriate management cycle, expatriate adjustment, and issues and trends. Findings have shown that, most of the studied companies do have a proper expatriation process that in line with the theories however, companies also shown certain deviation from the literature where reality is not always the same as theories. For instances, they do pay attention to the expatriates and family members' ability to adjust during planning and have a comprehensive selection process and selection criteria which are important to identify the right person for the right assignment. They also provide the crosscultural training and supports to the expatriates and family members. However, deviations from the literature include the repatriation supports provided is not as extensive as the theories suggested, expatriate has no guarantee of career development, and there are additional issues in the expatriation process which have not been discussed in past research such as local employees do face pressure and adjustment process when the expatriates holding the critical positions in the company keep on changing.